Development of Science E-Modules Based on Socio-scientific Issues Integrated with The Quran Verses to Establish Pancasila Student Profiles - Diniya Diniya; Zarkasih Zarkasih; Niki Dian Permana; Indria Kirana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Science learning uses more teaching materials in the form of textbooks, student worksheet and animated videos and still rarely use module or electronic module teaching materials. The role of teaching materials is very important for the continuity of the process science learning in class Technological advances and developments over time, teaching materials used in the learning process have also experienced developments expressed in the form of technology and digital formats. Teaching materials must be based on efforts to instill moral values in schools and integrate Al-Quran verses and social life into learning materials. This research aims to develop a science e-module based on Socio-scientific Issues (SSI) integrated with Islamic values to establish the Pancasila student profile. The research uses research and development methods according to Borg and Gall. Based on validation of the instrument contents by 3 experts, the instrument is suitable for use. Based on the results of the e-module content validation carried out by 3 experts, the e-module is suitable for use in science learning. Based on practicality results by 6 teachers in 6 junior high schools, it was found that the practicality value was 91.82%, which means that e-modules are very practical to try out in science learning. Based on 130 student responses, the e-module was in value 93% which means the student response was very good towards the development of the e-module.Keywords: electronic module, socio-scientific issue (ssi), integration of quranic verses